New polynomials of knots - Prishlyak, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
For some knots and links with respect to regular isotopy, we introduce a new invariant, which is a Laurent polynomial in three variables. The properties of this invariant are studied.